Quantum Chemical Analysis of 3,5-Dimethyl-2,6-Diphenylpyridine and its Para Amino and Nitro Phenyl Derivatives Using Density Functional Theory (Indian Journal of Chemistry (IJC), 2024)
In this study, density functional theory calculations at the wB97XD/Def2TZVPP level were performed for 3,5-dimethyl-2,6-diphenylpyridine (1) compound and its para amino phenyl (2), para nitro phenyl (3), para amino nitro phenyl (4) derivatives. Global reactivity descriptors, namely, ionization potential, electron affinity, electronegativity, chemical potential, chemical hardness, softness, and electrophilicity index, were calculated using the highest occupied molecular orbital (HOMO) and lowest unoccupied molecular orbital (LUMO) energies. In addition, molecular electrostatic potential surfaces, Mulliken and natural charges, natural bond orbitals were analyzed. Furthermore, ultraviolet–visible (UV–Vis) absorption characteristics and nonlinear optical parameters, viz. dipole moment, polarizability, and hyperpolarizability, were calculated. The range of the energy-gap values (ELUMO − EHOMO) was 6.9470–8.8026 eV, indicating the chemical stability of 1–4, with 4 exhibiting the smallest energy gap, lowest hardness, and most softness. According to the UV–Vis analysis, p→p* transitions dominate, and in the HOMO–LUMO transition, the wavelength increases in the order of 4 > 3 > 2 > 1. The hyperpolarizability values change drastically, with the βtotal/βurea ratio for 1, 2, 3, and 4 being 2.7, 28, 25, and 50, respectively. These materials, especially 4, are promising for optoelectronics and industrial applications.